Joint assimilation of eddy covariance flux measurements and FAPAR products over temperate forests within a process‐oriented biosphere model. Issue 9 (30th September 2015) - Bacour, C.; Peylin, P.; MacBean, N.; Rayner, P. J.; Delage, F.; Chevallier, F.; Weiss, M.; Demarty, J.; Santaren, D.; Baret, F.; Berveiller, D.; Dufrêne, E.; et al.
Abstract: We investigate the benefits of assimilating in situ and satellite data of the fraction of photosynthetically active radiation (FAPAR) relative to eddy covariance flux measurements for the optimization of parameters of the ORCHIDEE (Organizing Carbon and Hydrology in Dynamic Ecosystem) biosphere model. We focus on model parameters related to carbon fixation, respiration, and phenology. The study relies on two sites—Fontainebleau (deciduous broadleaf forest) and Puechabon (Mediterranean broadleaf evergreen forest)—where measurements of net carbon exchange (NEE) and latent heat (LE) fluxes are available at the same time as FAPAR products derived from ground measurements or derived from spaceborne observations at high (SPOT (Satellite Pour l′Observation de la Terre)) and medium (MERIS (MEdium Resolution Imaging Spectrometer)) spatial resolutions. We compare the different FAPAR products, analyze their consistency with the in situ fluxes, and then evaluate the potential benefits of jointly assimilating flux and FAPAR data. The assimilation of FAPAR data leads to a degradation of the model‐data agreement with respect to NEE at the two sites. It is caused by the change in leaf area required to fit the magnitude of the various FAPAR products. Assimilating daily NEE and LE fluxes, however, has a marginal impact on the simulated FAPAR. The results suggest that the main advantage of including FAPAR data is the ability to constrain the timing of leaf onset and senescence for deciduous ecosystems, which is best achieved by normalizing FAPAR time series. The joint assimilation of flux and FAPAR data leads to a model‐data improvement across all variables similar to when each data stream is used independently, corresponding, however, to different and likely improved parameter values. Key Points: Compatibility of in situ NEE and LE data and various FAPAR products through model‐data fusion FAPAR mainly constrains phenology; when assimilated alone, it may degrade the modeled fluxes Combining the two data streams is preferable for improving a process‐based vegetation model